PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA PELAJARAN SENI RUPA KELAS V SEKOLAH DASAR - Muhammad Sirojudin, Aceng; Rengganis, Ira; Arasy Magistra, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning interest of fifth-grade elementary school students in art lessons, specifically on the topic of recognizing various decorative patterns (ragam hias) from different regions of Indonesia. This issue is attributed to a lack of innovation in the teaching process, including the use of conventional learning media that relies solely on textbooks. The aim of this study is to develop interactive multimedia based on Problem-Based Learning (PBL) to increase students’ learning interest in art subjects in fifth grade. To address this issue, the study employs a Design and Development method using the PPE (Planning, Production, Evaluation) development model. Data were collected through observation, interviews, expert validation questionnaires, and student learning interest questionnaires, and analyzed using both qualitative and quantitative approaches. The product developed is an interactive multimedia tool that presents materials on traditional decorative patterns from various regions of Indonesia, structured according to the PBL syntax. Expert validation results indicate that the media is classified as "highly feasible" for use in learning, while the student learning interest questionnaire results show a significant increase, falling into the "high" category. Thus, this PBL-based interactive multimedia is effective in enhancing the learning interest of fifth-grade elementary school students in art education.